2005
DOI: 10.1128/aem.71.9.5022-5028.2005
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Damage and Microbial Inactivation by Chlorine in the Absence and Presence of a Chlorine-Demanding Substrate

Abstract: The relationship between cell inactivation and membrane damage was studied in two gram-positive organisms, Listeria monocytogenes and Bacillus subtilis, and two gram-negative organisms, Yersinia enterocolitica and Escherichia coli, exposed to chlorine in the absence and presence of 150 ppm of organic matter (Trypticase soy broth). L. monocytogenes and B. subtilis were more resistant to chlorine in distilled water. The addition of small amounts of organic matter to the chlorination medium drastically increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
166
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(184 citation statements)
references
References 16 publications
14
166
0
4
Order By: Relevance
“…The toxicity of chlorine to the biofilm and planktonic diatoms cells was reported by Nanchariah et al (2008). Membrane damage and microbial inactivation by chlorine in the presence and absence of a chlorine denaturing the substrate was also reported by Virto et al (2005). However, there is no information on the effect of chlorine on other factors, such as cell hydrophobicity, cell surface charge and EPS production that are involved in bacterial adhesion to surfaces.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The toxicity of chlorine to the biofilm and planktonic diatoms cells was reported by Nanchariah et al (2008). Membrane damage and microbial inactivation by chlorine in the presence and absence of a chlorine denaturing the substrate was also reported by Virto et al (2005). However, there is no information on the effect of chlorine on other factors, such as cell hydrophobicity, cell surface charge and EPS production that are involved in bacterial adhesion to surfaces.…”
Section: Introductionmentioning
confidence: 94%
“…Sodium hypochlorite is a nonspecific broad-spectrum oxidizing biocide and affects metabolic and physiological processes of microorganisms by causing damage to the cell membrane, proteins and nucleic acids (Phe et al 2004, Virto et al 2005, Nancharaiah et al 2008. It is highly effective against Gram-positive and Gramnegative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have shown that some treatments (e.g. alkaline treatment, heating, chemical treatment and ultrasound) can damage microbial cell membranes (Goodford, 1971;Virto et al, 2005;Tachibana et al, 1999;Sampathkumar et al, 2003). For example, Sampathkumar et al (2003) found that high pH (>10.0) during trisodium phosphate treatment causes membrane damage of S. enterica.…”
Section: Damage Of Cell Membranes In Eps Extractionmentioning
confidence: 99%
“…To quantify the intracellular UV materials released from E. coli K-12, the extracts from treated and untreated cells containing the UV materials were measured at 260 and 280 nm with a Spectrophotometer (DUR 530, Beckman Coulter, Fullerton CA) according to published reports [29,30].…”
Section: Leakage Of Bacteria Intracellular Ultraviolet (Uv)-absorbingmentioning
confidence: 99%